Albumin amplifies the dioxetane (AMPPD) chemiluminescence triggered by alkaline phosphatase: Light emerging from protein cavities - Barison, Leonardo Almeida [UNESP]; Yoguim, Maurício Ikeda [UNESP]; de Souza, Aguinaldo Robinson [UNESP]; Morgon, Nelson Henrique; Ximenes, Valdecir Farias [UNESP] (Elsevier, 2025)
AMPPD is an abbreviation for 3-(2′-spiroadamantyl)-4-methoxy-4-(3-phosphoryloxy)-phenyl-1,2-dioxetane, a thermally stable 1,2-dioxetane derivative widely used as a chemiluminescent probe in clinical laboratories for enzyme immunoassays. AMPPD is a substrate for alkaline phosphatase (ALP), the enzyme that catalyzes the remotion of the phosphoryl group of AMPPD, triggering light emission. This study investigated the impact of albumins on the AMPPD:ALP system and found that human serum albumin (HSA) increases the light emission efficiency of AMPPD:ALP by around 100 times. The efficiency of light enhancement varied depending on the type of albumin, with bovine (BSA), porcine (PSA), and rabbit (RSA) serum albumins being less effective than HSA. We conducted experiments to demonstrate that once hydrolyzed by ALP, the dephosphorylated AMPPD diffuses to site I of HSA. By studying the photophysical properties of the phenol ester generated after AMPPD cleavage, we found that its complexation with HSA caused a significant increase in its fluorescent efficiency, which explains the amplification of the chemiluminescence. Resonance energy transfer from the excited phenol ester to coumarin-153 was detected, confirming the presence of both molecules in the protein cavity. Hence, introducing fluorescent acceptors into the reaction system can adjust the emission wavelength. Besides the first direct evidence of albumin as an enhancer for chemiluminescence, the results highlight the potential interference of albumins on AMPPD-mediated assays and new biotechnological applications.
Keywords: Alkaline phosphatase; AMPPD; Chemiluminescence; Human serum albumin; Light enhancer; Resonance energy transfer